An Empirical Study on Measuring Operating Efficiency and Revenue of Real Estate Assets in the UAE Using Data Envelopment Analysis - Alafeefi, Abdulrahman (2019)
The main focus of this thesis is building assets in the United Arab Emirates as a representative of emerging real estate markets. Research conducted in this thesis tackles the issue of efficiency in building assets. There is an extreme lack of studies investigating the performance of building assets in emerging markets in the Middle East. In the last couple of decades, the United Arab Emirates has witnessed an accelerated growth in all economic aspects. The population exploded from barely 3 million to almost 10 million. This growth of population forced the real estate industry to grow as well. As a result, investment in real estate became one of the main norms. Nevertheless, comparing the performance of real estate building assets is not an easy task due to the lack of necessary studies. This thesis tries to fill this gap by investigating efficiency in real estate. Data envelopment analysis was used as the main methodology in this research. In addition, data collection of 57 building assets was conducted. Results showed that most of the building assets in this investigation can be considered moderate with regard to efficiency in terms of Capital Expenditures metrics. On the other hand, Operational Expenditures metrics experience a wider range of efficiency values, indicating that the building assets require improvement. Finally, this thesis contributed to expanding the definition of real estate performance outside financial performance and investigating the uniqueness of the efficiency of building assets in emerging economies by utilising local data only.